Conceptual metaphors in North African French-speaking news discourse about COVID-19 - Lahlou, Hicham; Rahim, Hajar Abdul (Indonesian Journal of Applied Linguistics, 2022)
Conceptual metaphors have received much attention in research on discourse about infectious diseases in recent years. Most studies found that conceptual metaphors of war dominate media discourse about disease. Similarly, a great deal of research has been undertaken on the new coronavirus, i.e., COVID-19, especially in the English news discourse as opposed to other languages. The present study, in contrast, analyses the conceptual metaphors used in COVID-19 discourse in French-language newspapers. The study explored the linguistic metaphors used in COVID-19 discourse in these newspapers and conceptual metaphors that underlie and motivate them, using a conceptual metaphor theory framework (CMT). Therefore, two North African French-language newspapers, namely LibÃ©ration, published in Morocco, and La Presse de Tunisie, published in Tunisia, formed the corpus of the current study. The results showed that the most frequent framing of COVID-19 was in terms of WAR, followed by DISASTER and KILLER, respectively.